Global Positioning System (GPS) – A Study - Bangshidhar Goswami; Jaydev Banerjee, Tarun Kumar Goswami, Deep Sen (Journal of Power Electronics and Devices, 2021)
This article is the study of a global positioning system (GPS). Scripture issued utility has the scope of user definitive position, navigation, and time (PNT) services. The descriptive issued system has consisted of three segments, given by space segment, control segment, and user segment. GPS has signified to scheme allocation of position in the earth. GPS satellites encircle earth twice/day in precise orbits. Each satellite has been prescribed to transmit signal and orbital parameters towards GPS devices, henceforth, GPS has been summarized to decode and compute the location of the satellite. The principle of GPS is to determine the best possible accuracy subjectively about a point in space, otherwise, geographical latitude, longitude, and elevation above sea level. A-Rated GPS monitor has been scoped to access system-wide disturbances in power systems. Usual trade for the utility industry has been subjected to adopted large-scale and complex security from the power system. Studied fame has scripted issued protection and control actions toward major power systems thereby disturbance has prompted schedule about inform of power system degradation. Obvious GPS counseling has schemed to restore the system to a normal state, and logical minimization of disturbances. Succeed by fast has been additional soft algorithmic has designed as adage towards control actions, thus suggestive issued front has rated as dynamic simulation software applicable for off-line analysis.